Identification of Operational Risks in Improving the Quality of Education - Dhea Aulia Shofitri; Wahyu Hidayat; Novia Yanti; M. Hidayat Ediz (Ri'ayatu Al-Qur'an: Jurnal Pendidikan Islam, 2024)
The main discussion of this research is identifying operational risks in improving the quality of education at Madrasah Tsanawiyah as well as how to control and evaluate these risks. Madrasah or other educational institutions that have the same eligibility requirements as any organization. Operational risk control is a way of managing risk that goes hand in hand with various aspects of the company, where risks can be managed or reduced until the amount of risk cannot be completely eliminated. This research uses qualitative research methods through a descriptive approach. This research aims to determine and describe operational risks in improving the quality of education at Madrasah Tsanawiyah, as the results of the author's research conclude that there are several operational risks identified and the institution already knows how to control and evaluate to follow up on these matters.